1998
DOI: 10.1128/mcb.18.2.1055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the p53-Dependent Postmitotic Checkpoint following Spindle Disruption

Abstract: The p53 tumor suppressor gene product is known to act as part of a cell cycle checkpoint in G 1 following DNA damage. In order to investigate a proposed novel role for p53 as a checkpoint at mitosis following disruption of the mitotic spindle, we have used time-lapse videomicroscopy to show that both p53 ؊/؊ fibroblasts fail to arrest in response to nocodazole treatment and become polyploid. Moreover, p21 is required to a similar extent to maintain cell cycle arrest after either nocodazole treatment or irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
395
1
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 473 publications
(440 citation statements)
references
References 39 publications
(50 reference statements)
33
395
1
4
Order By: Relevance
“…Vanadium unlike chromium is known to inhibit microtubule assembly and induce tubulin depolymerization (Ramirez et al, 1997). Lanni and Jacks (1998) showed that adaption to another microtubule destabilizing drug (nocodazole) caused a p53-dependent G1 arrest. It is therefore possible that abnormal p53 signalling in hTERT þ cells was partly responsible for the tetraploidy caused by V (V).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…Vanadium unlike chromium is known to inhibit microtubule assembly and induce tubulin depolymerization (Ramirez et al, 1997). Lanni and Jacks (1998) showed that adaption to another microtubule destabilizing drug (nocodazole) caused a p53-dependent G1 arrest. It is therefore possible that abnormal p53 signalling in hTERT þ cells was partly responsible for the tetraploidy caused by V (V).…”
Section: Metal-induced Genomic Instabilitymentioning
confidence: 99%
“…The changes in PTX-2-treated p53-positive cells closely resemble those in normal cells treated with spindle inhibitors, which enter into tetraploid G 1 state (Lanni and Jacks, 1998). Cyclins D and E were increased, but cyclins A and B were decreased following PTX-2 treatment (Figure 2a), implying that those cells arrested at G 1 checkpoint.…”
Section: Discussionmentioning
confidence: 70%
“…After a delay period, cells eventually escape from this block (a process termed 'mitotic slippage'), and exit mitosis without a proper segregation of sister chromatids and cytokinesis (Jordan et al, 1991(Jordan et al, , 1996Torres and Horwitz, 1998). Therefore, spindle-damaged cells arrests at G 1 -like state with an intact nucleus containing 4N DNA, but without ever completing mitosis (Minn et al, 1996;Lanni and Jacks, 1998). This is recently termed as tetraploid G 1 state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations